Facile and controlled synthesis of stable water-soluble cupric sulfide quantum dots for significantly inhibiting the proliferation of cancer cells. Issue 27 (17th June 2015) - Shuang, Wei; Wang, Xiaobing; Wang, Ge; Guo, Yuming; Wang, Kui; Yang, Gai; Zhu, Lin; Yang, Lin
Abstract : Stable amorphous and crystalline copper sulfide quantum dots (QDs) were obtained controllably by a facile two-step method. These QDs exhibited anti-proliferation activities on cancer cells. Abstract : Amorphous and crystalline copper sulfide quantum dots (QDs) with good water-solubility were obtained controllably by a novel hydrolysis strategy. These QDs exhibited anti-proliferation activities on cancer cells rather than normal cells and the biological activities are related to their polymorphs. Our study opens up new avenues for fabricating stable water-soluble metal sulfide QDs.